Identifying the Key Value of Urban Architectural Heritages vis-a-vis Human Awareness: Case Study in Hanoi - Dao Thi, Nhu (Journal of Urban Culture Research, 2023)
Conservation of urban architectural heritage works (UAH) is an important test for cities to increase their cultural and economic competitiveness. However, UAH preservation mostly focuses on physical value, which results in a contradiction between conservation and development. Moreover, new contexts of 4.0 technology and urbanization are deepening the impermanence, transformation of all things, in which of people and their awareness - the beneficiaries of UAHs. Therefore, heritage conservation is facing a big problem related to the truly worthy values of UAH that need to be preserved to meet the development needs, society’s change and the growing maturity of people’s awareness. Applying Oriental theories on the code of life, in combination with some Western thoughts on human awareness process and a practical case of community’s awareness of UAHs’s value in Hanoi, the article explores and identifies the key value of UAHs which is expected to solve the above problem, reaching sustainable targets.